Survival of cancer survivors with a new pancreatic cancer diagnosis. (8th June 2022) - Pruitt, Sandi L.; Tavakkoli, Anna; Zhu, Hong; Heitjan, Daniel F.; Gerber, David E.; Singal, Amit G.; Halm, Ethan A.; Beg, Muhammad Shaalan; Maddineni, Bhumika; Kansagra, Ankit J.; Murphy, Caitlin C.
Abstract: Background: Persons newly diagnosed with pancreas cancer and who have survived a previous cancer are often excluded from clinical trials, despite limited evidence about their prognosis. We examined the association between previous cancer and overall survival. Methods: This US population‐based cohort study included older adults (aged ≥66 years) diagnosed with pancreas cancer between 2005 and 2015 in the linked Surveillance, Epidemiology, and End Results‐Medicare data. We used Cox proportional hazards models to estimate stage‐specific effects of previous cancer on overall survival, adjusting for sociodemographic, treatment, and tumor characteristics. Results: Of 32, 783 patients, 18.7% were previously diagnosed with another cancer. The most common previous cancers included prostate (29.0%), breast (18.9%), or colorectal (9.7%) cancer. More than half of previous cancers (53.9%) were diagnosed 5 or more years prior to pancreas cancer diagnosis or at an in situ or localized stage (47.8%). The proportions of patients surviving 1, 3, and 5 years after pancreas cancer were nearly identical for those with and without previous cancer. Median survival in months was as follows for those with and without previous cancer respectively: 7 versus 8 (Stage 0/I), 10 versus 10 (Stage II), 7 versus 7 (Stage III), and 3 versus 2 (Stage IV). Cox models indicated that patients with previous cancer had very similar or statistically equivalent survival to those with no previous cancer. Conclusions: Given nearly equivalent survival compared to those without previous cancer, cancer survivors newly diagnosed with pancreas cancer should be considered for inclusion in pancreas cancer clinical trials. Abstract : In this population‐based cohort of 32, 783 patients diagnosed with pancreas cancer, nearly one in five were previously diagnosed with another cancer; commonly prostate, breast, or colorectal. Survival was nearly equivalent among those with and without previous cancer.